Fiqh Al-Bī’ah As a Normative Foundation for Sustainable Green Economy Development In Muslim Societies - Mohammad Romli; Muhammad Ikhlas Rosele; Samheri (CV. Creative Tugu Pena, 2026)
This study aims to examine the normative potential of fiqh al-Bī’ah and maqāṣid al-sharī‘ah as an Islamic ethical framework for strengthening sustainable green economy development in Muslim societies. Using a qualitative normative-conceptual approach, this research employs systematic literature analysis of classical Islamic jurisprudence, contemporary Islamic economic thought, and recent global sustainability studies. The findings reveal that fiqh al-Bī’ah provides a coherent normative structure through principles such as khalīfah, amānah, mīzān, iṣlāḥ, and lā ḍarar wa lā ḍirār, which are conceptually aligned with key green economy indicators, including ecological balance, resource efficiency, and intergenerational equity. Furthermore, the study demonstrates a strong normative convergence between maqāṣid al-sharī‘ah and sustainable development goals, particularly in safeguarding life, wealth, future generations, and environmental integrity. Importantly, maqāṣid al-sharī‘ah functions as a critical evaluative framework capable of assessing the social justice implications of market-oriented green economy models. This study contributes theoretically by positioning Islamic environmental jurisprudence not merely as moral guidance but as an operational normative foundation for sustainable economic transformation. Practically, the findings offer policy-relevant insights for integrating Islamic ethical values into green economy strategies, Islamic finance, and ESG-based development initiatives. The research concludes that an Islamic value-based green economy represents a viable, inclusive, and ethically grounded pathway for addressing contemporary environmental challenges